2017
DOI: 10.3390/app7050443
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents and Biological Activities of Essential Oils of Hydnora africana Thumb Used to Treat Associated Infections and Diseases in South Africa

Abstract: Hydnora africana (HA) Thumb is a member of the genus Hydnora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
1
12
0
1
Order By: Relevance
“…Chen et al [57] also reported that methyl benzoate has insecticidal properties against pest insects and mites. Save et al [58] reported that 1, 2-benzenedicarboxylic acid, butyl octyl ester, can be used in drug development for arthritis, microbial allergies, and cancer, whereas it can also be used as an antioxidant and antimicrobial agent [59]. 8-Octadecenoic acid methyl ester (E) showed antioxidant and antimicrobial activity and also effects of the serum lipid in women during lactation period [60,61].…”
Section: Gas Chromatography-mass Spectrometry Analysismentioning
confidence: 99%
“…Chen et al [57] also reported that methyl benzoate has insecticidal properties against pest insects and mites. Save et al [58] reported that 1, 2-benzenedicarboxylic acid, butyl octyl ester, can be used in drug development for arthritis, microbial allergies, and cancer, whereas it can also be used as an antioxidant and antimicrobial agent [59]. 8-Octadecenoic acid methyl ester (E) showed antioxidant and antimicrobial activity and also effects of the serum lipid in women during lactation period [60,61].…”
Section: Gas Chromatography-mass Spectrometry Analysismentioning
confidence: 99%
“…Researchers have shown that the volatile oils of different plant organs have antitumorigenic, insecticidal, antifungal, anticarcinogenic, antibacterial, anti-inflammatory, antiparasitic, antiviral and antioxidant properties. [81,90,101,102,106] Table 2 represents the collection of literature data concerning essential oil composition of Laggera spe- Aerial EtOH Eudesmane sesquiterpenes: 1β,9β-Dihydroxy-4αH-eudesma-5,11(13)-dien-12-oic acid; 1β,3α-dihydroxyeudesma-5,11(13)-dien-12-oic acid; 2β-hydroxyilicic acid; Eudesmane sesquiterpene glucosides: Eudesmane sesquiterpenes: 3β,4α-Dihydroxy-7-epi-eudesm-11(13)-ene; 3αangeloyloxy-4α,11-dihydroxyeudesm-6-en-8-one; 3α-(2',3'-dihydroxy-2'-methylbutanoyl)-4,11-dihydoxy-6,7-dehydroeudesman-8-one; 3α-(3'-chloro-2'hydroxy-2'-methylbutanoyl)cuauthemone [65] [a] NR, Not reported. cies from different countries.…”
Section: Essential Oil Constituentsmentioning
confidence: 99%
“…H. arabica is distributed from Southern Oman (Dhofar region) to Yemen on Acacia species [ 1 ]. H. africana is distributed in Namibia, Swaziland, Nigeria, Kenya, Zimbabwe, Uganda, Madagascar, Saudi Arabia, South Africa, and Ethiopia [ 8 , 12 , 25 , 43 , 47 , 48 ]. H. abyssinica is the most widely distributed species in Namibia, Northern Botswana, Zimbabwe, Zaire, Tanzania, Kenya, Ethiopia, Somalia, Sudan, and the Arabian Peninsula [ 11 , 23 , 24 , 29 , 40 , 49 , 50 , 51 ].…”
Section: Host Specificity Concerning Species Distributionmentioning
confidence: 99%
“…Moreover, the flowers of H. abyssinica are used as wild food and in traditional medicine in South Yemen [ 24 ]. Therapeutic properties, for instance, antibacterial, antifungal, antioxidant, and antiproliferative activities, have been reported in H. abyssinica and H. africana [ 25 , 26 , 27 , 28 ]. Regardless of the ethnobotanical value and medicinal significance of the Hydnora species, little effort has been made to integrate all of the relevant available data.…”
Section: Introductionmentioning
confidence: 99%